STUDY THE ANTIMICROBIAL AND ANTIADHESIVE ACTIVITY OF PURIFIED BIOSURFACTANT PRODUCED FROM LACTOBACILLUS PLANTARUM AGAINST PATHOGENIC BACTERIA - Jameel, A . A.; Haider, N. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to purification the biosurfactant that produced from Lactobacillus plantarum isolated from clinical samples of iraqi healthy women by column chromatography through silica gel column (3.5 × 30 cm) using solvent system (chloroform : methanol, 2:1) and characterization the purified product by Thin layer chromatography (TLC), Fourier Transform Infrared Red spectroscopy (FTIR) and Gas chromatography (GC) mass then evaluated its antibacterial and anti-adhesive activity. The results shown the higher emulsification activity (E24%= 63) and lower the surface tension to 23 mN/m in synthetic MSM, while the natural media gave (E24% =71) and lower surface tension to 19 mN/m. The using TLC technique indicated presence of lipopeptide in the biosurfactant with Rf value = 0.82. Antibacterial and antiadhesion activities were evaluated against some pathogenic bacteria, including Pseudomonas aureginosa and Staphylococcus aureus. The results showed a higher inhibitory effect of biosurfactant at concentration 200 mg/ml on S. aureus and P. aeruginosa with the inhibition zone 27 mm and 33 mm respectively in BCDFTM media. While purified biosurfactant with concentration 200 mg/ml produced in MSM media had an effect on S. aureus and P. aeruginosa with the inhibition zone 21 mm, and 18 mm respectively. The anti-adhesion activity of purified biosurfactant against p.aeruginosa ranging from (34.70 ± 5.256) to (11.7 ± 9.7) produced from natural media BCDFTM and was higher than the anti-adhesion activity of purified biosurfactant against the same pathogen ranging from (46.95 ± 7.37) to (20.15 ± 2.805) produced in MSM.